Humanized CD19-Targeted Chimeric Antigen Receptor (CAR) T Cells in CAR-Naive and CAR-Exposed Children and Young Adults With Relapsed or Refractory Acute Lymphoblastic Leukemia. Issue 27 (20th September 2021) - Myers, Regina M.; Li, Yimei; Barz Leahy, Allison; Barrett, David M.; Teachey, David T.; Callahan, Colleen; Fasano, Christina C.; Rheingold, Susan R.; DiNofia, Amanda; Wray, Lisa; Aplenc, Richard; Baniewicz, Diane; et al.
Abstract : PURPOSE: CD19-targeted chimeric antigen receptor (CAR)–modified T cells demonstrate unprecedented responses in B-cell acute lymphoblastic leukemia (B-ALL); however, relapse remains a substantial challenge. Short CAR T-cell persistence contributes to this risk; therefore, strategies to improve persistence are needed. METHODS: We conducted a pilot clinical trial of a humanized CD19 CAR T-cell product (huCART19) in children and young adults with relapsed or refractory B-ALL (n = 72) or B-lymphoblastic lymphoma (n = 2), treated in two cohorts: with (retreatment, n = 33) or without (CAR-naive, n = 41) prior CAR exposure. Patients were monitored for toxicity, response, and persistence of huCART19. RESULTS: Seventy-four patients 1-29 years of age received huCART19. Cytokine release syndrome developed in 62 (84%) patients and was grade 4 in five (6.8%). Neurologic toxicities were reported in 29 (39%), three (4%) grade 3 or 4, and fully resolved in all cases. The overall response rate at 1 month after infusion was 98% (100% in B-ALL) in the CAR-naive cohort and 64% in the retreatment cohort. At 6 months, the probability of losing huCART19 persistence was 27% (95% CI, 14 to 41) for CAR-naive and 48% (95% CI, 30 to 64) for retreatment patients, whereas the incidence of B-cell recovery was 15% (95% CI, 6 to 28) and 58% (95% CI, 33 to 77), respectively. Relapse-free survival at 12 and 24 months, respectively, was 84% (95% CI, 72 to 97) and 74% (95% CI, 60 to 90) in CAR-naive and 74% (95% CI, 56 to 97) and 58% (95% CI, 37 to 90) in retreatment cohorts. CONCLUSION: HuCART19 achieved durable remissions with long-term persistence in children and young adults with relapsed or refractory B-ALL, including after failure of prior CAR T-cell therapy.